Sport-specific experience modulates perceived exertion but not enjoyment or workload in recreational 3 × 3 basketball - Lukonaitienė, Inga; Pernigoni, Marco; Kniubaitė, Audinga; Kreivytė, Rasa; Kamandulis, Sigitas; Conte, Daniele (Frontiers in Physiology, 2026)
This study aimed to investigate the differences of previous basketball-specific experience on perceived exertion, enjoyment, physiological, and physical responses during recreational 3 × 3 basketball in active young adults. Twenty-four healthy male participants were divided into two groups: those with basketball experience (9.6 ± 4.5 years) and those with minimal or no experience (0.7 ± 0.9 years). All participants completed a 10-min recreational 3 × 3 basketball match following official FIBA rules. Heart rate responses were monitored using Polar H10 heart rate straps to determine the percentage of maximal heart rate (%HRmax), while perceptual responses were assessed through the modified Borg RPE scale (0–10) and the Exercise Enjoyment Scale (1–7). Physical demands were captured using inertial measurement units (Catapult) and included PlayerLoad/min, accelerations, decelerations, changes of direction, and jumps. Between-group differences were analyzed using t-tests for normally distributed data or Mann–Whitney U tests otherwise. No significant differences were observed between experienced and non-experienced players for %HRmax, enjoyment, or physical activity metrics (p > 0.05). However, non-experienced participants reported significantly higher RPE values than their experienced counterparts (p = 0.005; r = 0.68, large effect size), indicating that prior sport-specific experience may affect the perceived difficulty of a given task, even when physiological and physical outputs are similar. In conclusion, these findings suggest that perceived exertion is more sensitive to prior sport-specific experience than physiological or physical measures, underlining the need to consider participants’ backgrounds when monitoring internal load. Overall, recreational 3 × 3 basketball remains a highly enjoyable activity across experience levels and may support adherence to long-term physical activity programs.